A Multiscale Porous 3D‐Fabric Evaporator with Vertically Aligned Yarns Enables Ultra‐Efficient and Continuous Water Desalination. (3rd August 2022) - Lei, Zhiwei; Zhu, Shifeng; Sun, Xuantong; Yu, Shaonan; Liu, Xuqing; Liang, Kun; Zhang, Xueji; Qu, Lijun; Wang, Lili; Zhang, Xiansheng
Abstract: Solar steam generation has emerged as an environment‐friendly and promising strategy to overcome the freshwater and energy crisis. However, simultaneously attaining the satisfied evaporation rate, durability and energy utilization in a single system is challengeable, but crucial to the practical application. Herein, inspired by the carpet weaving technique and benefiting from "fiber–yarn–fabric" hierarchical structures, a 3D fabric evaporator with vertical hemp‐yarn arrays is innovatively constructed, featuring a combined structure of multiscale pores from tunable spacing between adjacent fibers or yarns, the vertically aligned architecture coated with superhydrophilic MXene‐sandwiched layer and the adjustable side height/areas. These structures work cooperatively, surprisingly achieving the integrated functions of excellent light capture, the balanced evaporation area and vapor escape space, the additional energy adsorption from the environment and the salt exchange along or between micro/macro pores. Consequently, the 3D evaporator exhibits an outstanding evaporation rate (3.95 kg m −2 h −1 under one‐sun illumination) and extremely high outdoor evaporation (47.04 kg m −2 for 8 h), accompanied with outstanding salt‐resistance (continuous 120 h in 14% brine without salt accumulation), anti‐oilfouling and anti‐bacterial (efficiency over 99.9%) performances. Finally, through rationally assembling multi‐function modules with a condenser, an all‐in‐one "desalination–thermoelectricity–irrigation" platform is built, realizing the maximum utilization of steam condensation enthalpy. Abstract : A multiscale porous 3D‐fabric evaporator with vertically aligned hemp‐yarns is innovatively constructed and produces integrated functions of excellent light capture, fast escape of vapor, and the additional energy absorption from the environment, simultaneously achieving outstanding evaporation efficiency, anti‐fouling performance, and long‐term working stability. Further designation of an all‐in‐one "desalination–thermoelectricity–irrigation" platform makes the maximum utilization of steam condensation enthalpy available.